(untitled) (Acta Scientiarum. Agronomy, 2019)
The relationship between soil and health is important for populations that depend on the local environment to meet their nutritional needs. This study aimed to evaluate the concentrations of major and trace elements in the soils, edible parts of crops and urine of farmers in agroecological communities. We collected samples of soil, edible parts of crops and urine of farmers and family members in 23 crop fields in agroecological communities from northeast Brazil. These samples were analyzed to concentrations of Al, As, Ca, Cr, Cu, Fe, Hg, Mg, Zn, and Pb in urine and discriminant analysis and principal component analysis were used to assess the data. Concentrations of potentially toxic elements in soils and crops of agroecosystems were below regulatory levels. Farmers living in agroecological communities present most of the essential and toxic elements in urine within the reference ranges. In general, results showed that urinary concentration of toxic elements among farmers and their families were below allowable limits, which may be due to the agroecological practices.